Hit for Six - Warner, David and Black, J. S.; Illustrated by Faber, Jules (Australia Simon & Schuster, 2015)
Davey Warner bets his friend Sunil half his birthday money-bought lollies that he can hit six sixes in the upcoming battle against their club rivals, Shimmer Bay, for the No 1 spot on the ladder. But when he forgets to hand in his PE assignment on lawn bowls (the favourite sport of Mr Mudge, their Year Six teacher), Davey is banned from playing cricket until it.s. done
Include Illustrations
Keywords: Australia -- Children's stories -- Cricket stories